Fourth Cranial Nerve Palsy and Bilateral Acute Retinal Necrosis following Human Herpesvirus 6 Infection of the Central Nervous System*. (June 2014) - Papageorgiou, Eleni; Ch'ng, Soon; Kulkarni, Archana; Anwar, Samira; Empeslidis, Theodoros
Abstract Acute retinal necrosis (ARN) is a rare, potentially blinding condition typically affecting immunocompetent individuals. It is defined by the clinical triad of vitreous inflammation, occlusive vasculopathy, and progressive retinal necrosis, usually located in peripheral retina with circumferential extension. Varicella zoster virus (VZV), herpes simplex virus (HSV), Epstein-Barr virus (EBV) and occasionally cytomegalovirus (CMV) are the common causative agents of ARN. Reports of human herpesvirus 6 (HHV6) infection of the central nervous system (CNS) associated with ocular inflammatory disease are extremely rare. We here report the case of a 22-year-old immunocompetent male who presented with acute bilateral ARN and fourth nerve palsy, following HHV6 infection of the CNS and EBV infectious mononucleosis.